2020
DOI: 10.3390/drones4040068
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Transportation Using Unmanned Aerial Vehicles (UAVs) during Disasters in Japan

Abstract: Larger types of small unmanned aerial vehicles (UAVs) are beginning to be used in the United States and Europe for commercial transportation. Additionally, some blood product transport systems have been commercialized in Rwanda and other countries and used in pandemic operations for the coronavirus disease 2019 (COVID-19) in infected areas. Conversely, implementing goods transportation for commercial purposes in Japan has been difficult, especially in urban areas, due to national legislation. This study examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Relying on a higher degree of autonomy and the ability to perceive & act UAVs can be used to in varied domains. Some potential future examples include pest detection and control within agriculture, UAVs for pick up and drop off as an extension to logistics and on-demand delivery, autonomous UAV safeguards such as malicious-UAV detection and escort presented in [6], [92] and cargo as well as people pick up and drop off [93]. Within this context, researchers explore key enablers to such applications ranging from mobility and swarming behaviours for complicated tasks requiring multi-UAV operations [94] and automating the design of autonomous UAV swarms as a disruptive approach to tackle the problem of designing swarming behaviours to novel automated algorithm selection approaches [95].…”
Section: Other Emerging Hybrid Applicationsmentioning
confidence: 99%
“…Relying on a higher degree of autonomy and the ability to perceive & act UAVs can be used to in varied domains. Some potential future examples include pest detection and control within agriculture, UAVs for pick up and drop off as an extension to logistics and on-demand delivery, autonomous UAV safeguards such as malicious-UAV detection and escort presented in [6], [92] and cargo as well as people pick up and drop off [93]. Within this context, researchers explore key enablers to such applications ranging from mobility and swarming behaviours for complicated tasks requiring multi-UAV operations [94] and automating the design of autonomous UAV swarms as a disruptive approach to tackle the problem of designing swarming behaviours to novel automated algorithm selection approaches [95].…”
Section: Other Emerging Hybrid Applicationsmentioning
confidence: 99%
“…1,2 However, we have earlier reported that the transport of blood by drones can be advantageous in the last single distance of transport in the transport process. 3 We have considered the batoning of blood transport by multiple modes of transport. In particular, we suppose that the supply of blood over a wide region, especially in times of disaster, may include the transport of blood from aircrafts to other modes of transport, especially drones.…”
Section: Letter To the Editormentioning
confidence: 99%
“…The use of drones has been expanding the frontiers of scientific knowledge and other several activities, facilitating and improving procedures throughout numerous fields [1,2], among which are agriculture [3,4], ecological studies [5,6], nature photography [7], fisheries [8], disaster management and civil security applications [9], commercial delivery [10], and medical care activities [11]. For example, drones have been shown to be promissory tools for improving health care purposes such as transporting blood for transfusions, testing in pandemics, and other infectious disease matters [11,12]. Additionally, ecological studies about population dynamics and landscape imaging are among the most numerous activities utilizing drones as a revolutionary tool in science [13].…”
Section: Introductionmentioning
confidence: 99%